Method for preparing a coating based on copper powder with high laser utilization and coating

CN122466461BActive Publication Date: 2026-10-09TIANJIN UNIV OF TECH & EDUCATION (TEACHER DEV CENT OF CHINA VOCATIONAL TRAINING & GUIDANCE) +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610974314.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-09
Estimated Expiration
2046-07-01

AI Technical Summary

Technical Problem

[0005]现有技术中,通常通过提高激光功率、增大热输入或采用短波长复合激光等方式改善铜材料的成形质量,但前两类方法容易带来基材过热、熔池波动加剧、飞溅增多和能量浪费等问题;短波长激光虽可改善表层吸收,却仍需解决能量在粉末层内部沉积不足及整体工艺稳定性问题

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a method for preparing a coating based on high laser utilization rate copper powder and the coating. The method comprises the following steps: (1) preparation of Cu skeleton powder; Cu-Zn alloy powder is first cleaned by ultrasonic cleaning with an organic solvent, then treated by soaking in dilute acid, cleaned by water and dried, then the dried Cu-Zn alloy powder is added into a corrosion liquid under stirring to perform selective dealloying treatment of preferential dissolution of metal Zn, solid-liquid separation, ultrasonic cleaning, freezing drying, and heating to room temperature to obtain porous Cu skeleton powder; (2) the Cu skeleton powder is deposited on a substrate by laser cladding to form a coating. By constructing a porous Cu skeleton structure, the method increases multiple reflections and effective action paths of laser in the powder, improves the energy utilization rate of laser and powder, and realizes the synergistic improvement of the coating thickness and the conductivity while ensuring the formation of a close metallurgical bond with the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of coating preparation, and specifically to a method for preparing a coating based on copper powder with high laser utilization and the coating itself. Background Technology

[0002] In current-carrying friction components such as slip rings, iron-based materials such as 45 steel or Q235 steel have good load-bearing capacity and wear resistance, but their poor conductivity and high resistivity make them prone to increased contact resistance and localized temperature rise during current-carrying friction, which can induce arc erosion, causing surface damage or even scrapping of the slip ring. Since the slip ring and carbon brush pair typically experience relatively small loads, the ultimate load-bearing capacity of the coating is not a primary concern during service; rather, higher requirements are placed on surface conductivity, current-carrying stability, and resistance to arc erosion. Therefore, using copper alloys with excellent conductivity and certain self-lubricating properties as surface coating materials has clear application value.

[0003] Laser cladding, as a surface repair and strengthening method, can form a coating with good adhesion to the substrate in situ, making it suitable for constructing functional layers on the surface of collector rings. However, the most mature and widely used lasers in current industrial applications are still mainly near-infrared fiber lasers with wavelengths of approximately 1µm. Existing research shows that copper's initial absorption rate for laser light in the approximately 1030-1070nm wavelength range is typically less than 5%, while its reflectivity can reach approximately 95%, significantly lower than its attraction to short-wavelength lasers in the 450-515nm range. This indicates that when using a 1064nm laser to prepare copper or copper alloy coatings, the incident energy is not simply a matter of "low utilization," but rather faces difficulties in energy coupling and absorption instability from the initial stage.

[0004] Furthermore, when a 1064nm laser acts on copper alloy powder or copper-based surfaces, the coexistence of low initial absorption and high thermal conductivity often requires higher power densities to establish an effective molten pool during the cladding process. Once local melting or vaporization occurs, the absorption behavior, evaporation backpressure, and molten pool flow state change rapidly, making the process prone to shifting from a conduction mode to a keyhole mode, resulting in poor molten pool stability. This instability not only causes "powder not melting" or "insufficient melting," but also further induces a series of forming defects such as spatter, porosity, thermal ablation, lack of fusion, cracks, and poor interfacial bonding, ultimately affecting the coating's density, thickness uniformity, and electrical conductivity. Existing studies on copper laser welding, laser cladding, and additive manufacturing have all indicated that process instability caused by low absorption, keyhole oscillation, and evaporation backpressure are important causes of porosity, spatter, and forming defects.

[0005] In existing technologies, the forming quality of copper materials is typically improved by increasing laser power, increasing heat input, or using short-wavelength composite lasers. However, the first two methods are prone to problems such as substrate overheating, increased molten pool fluctuations, increased spatter, and energy waste. While short-wavelength lasers can improve surface absorption, the issues of insufficient energy deposition within the powder layer and overall process stability still need to be addressed. Therefore, how to enhance the effectiveness of 1064nm lasers in high-reflectivity copper alloy powders without excessively increasing total heat input, improve laser propagation and energy deposition behavior within the powder layer, reduce defects such as spatter, porosity, and incomplete melting, and achieve stable preparation of highly conductive copper-based coatings remains a pressing technical problem to be solved in this field. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing coatings based on copper powder with high laser utilization, and the resulting coating. The method involves preferentially dissolving Zn in Cu-Zn alloy powder to prepare Cu powder with a porous framework structure. This porous structure allows 1064nm laser light to penetrate the powder interior, resulting in multiple reflections and repeated interactions, thereby extending the effective interaction path between the laser and the material and increasing the light-receiving surface area. This significantly improves the laser energy absorption efficiency, which, when used for powder melting and cladding construction, helps form a more stable molten pool without excessively increasing heat input, thus increasing the coating thickness. Simultaneously, this method improves the powder melting behavior, reduces spatter and incomplete fusion defects, and promotes a good metallurgical bond between the cladding layer and the high-reflectivity substrate, ultimately achieving a simultaneous increase in coating thickness and conductivity.

[0007] To achieve the above objectives, the specific implementation scheme of the present invention is as follows:

[0008] The first aspect of the present invention is to provide a method for preparing a coating based on copper powder with high laser utilization, comprising the following steps:

[0009] (1) Preparation of Cu skeleton powder: Cu-Zn alloy powder was first ultrasonically cleaned with organic solvent, then soaked in dilute acid, washed with water and dried. Then, under stirring conditions, the dried Cu-Zn alloy powder was added to the corrosion solution for selective dealloying treatment with preferential dissolution of metallic Zn. Solid-liquid separation, ultrasonic cleaning, freeze drying and then heated to room temperature were obtained to obtain Cu skeleton powder.

[0010] (2) The Cu skeleton powder is deposited on the substrate by laser cladding to form a coating.

[0011] This invention employs chemical reagents to selectively dealloy Cu-Zn composite powder, preferentially dissolving Zn and inhibiting excessive Cu corrosion under the action of corrosion inhibitors, thereby preserving the Cu powder with a porous framework structure. The nanoscale pores formed in this framework allow 1064 nm wavelength laser light to penetrate the powder interior, undergoing multiple reflections and scatterings between the pore walls. This reduces direct laser dissipation on the highly reflective outer surface, significantly improving the effective energy deposition of the laser in the powder layer. Simultaneously, the porous framework structure increases the specific surface area of ​​the powder, which is beneficial for improving the light-receiving area and melting uniformity, enabling efficient absorption of laser energy for powder melting and cladding construction. Without excessively increasing heat input, this method promotes the formation of a stable molten pool, increases coating thickness, improves powder melting behavior, reduces spatter and incomplete fusion defects, and promotes good metallurgical bonding between the cladding layer and the highly reflective substrate. Therefore, the coating prepared using the method of this invention has superior forming quality and overall performance.

[0012] As a preferred implementation, step (1)

[0013] The Zn content in the Cu-Zn alloy powder is 30-40 wt%;

[0014] The Cu-Zn alloy powder has a particle size of 45-100 μm.

[0015] As a preferred implementation, step (1)

[0016] The organic solvent is selected from at least one of propanol and acetone;

[0017] The duration of one ultrasonic cleaning cycle is 10-30 minutes;

[0018] The dilute acid is a 3-8 wt% dilute hydrochloric acid solution;

[0019] The dilute acid soaking time is 50-100 seconds;

[0020] The drying process is carried out at a temperature of 50-65℃.

[0021] As a preferred implementation, step (1)

[0022] The corrosive solution comprises an oxidant, an inorganic acid, a corrosion inhibitor, and water; the oxidant is H2O2; the inorganic acid is H2SO4; and the corrosion inhibitor is benzotriazole.

[0023] In the corrosive solution, the concentration of the oxidant in water is 25-35 wt%; the concentration of the inorganic acid in water is 0.5-1 mol / L; and the concentration of the corrosion inhibitor in water is 0.2-0.5 g / L.

[0024] As a preferred implementation, step (1)

[0025] The stirring speed is 180-250 rpm;

[0026] The ratio of dried Cu-Zn alloy powder to etching solution is 1g:40-60mL;

[0027] The selective dealloying treatment was performed at room temperature.

[0028] The selective dealloying treatment time is 25-60 min;

[0029] The solid-liquid separation method is filtration separation.

[0030] As a preferred implementation, step (1)

[0031] The cleaning solution for secondary ultrasonic cleaning includes water, ethanol, and Na2CO3; wherein the volume ratio of water to ethanol is 3-1:1; and the mass ratio of water to Na2CO3 is 50-100:1.

[0032] The second ultrasonic cleaning time is 15-20 minutes;

[0033] The freeze-drying time is 2-6 hours;

[0034] After freeze-drying, the air temperature rises to room temperature.

[0035] The porosity of the Cu framework powder is 60-80%;

[0036] The average pore diameter of the Cu skeleton powder is 5-10 μm.

[0037] As a preferred implementation, step (2)

[0038] The base material is selected from 45 steel or Q235 steel;

[0039] The laser used for laser cladding is a laser with a wavelength of 1064 nm;

[0040] The laser power of the laser cladding is 1500-3000W;

[0041] The powder feeding rate for laser cladding is set to 5-25 g / min.

[0042] As a preferred implementation, step (2)

[0043] The angle between the laser head nozzle of the laser cladding and the horizontal plane of the substrate is 75-85 degrees;

[0044] The distance between the laser head nozzle and the substrate in the laser cladding is set to 13-20mm;

[0045] The scanning speed of the laser cladding is 10-20 mm / s.

[0046] A second aspect of the present invention is to provide a coating material prepared by the method described in the first aspect of the present invention, wherein the coating material has a coating thickness of 800-1000 micrometers;

[0047] The conductivity of the coating material reaches 82% IACS or higher; preferably 87%~90% IACS.

[0048] A third aspect of this invention is to provide the application of the coating material described in the second aspect of this invention in a current-carrying friction component; preferably, the current-carrying friction component is a slip ring. For example, in current-carrying friction components such as slip rings, the aforementioned porous Cu framework powder can effectively repair surface damage by employing laser cladding technology with a wavelength of 1064 nm. The coating surface obtained by the porous Cu framework powder of this invention is dense and free of obvious cracks and other defects. Detailed Implementation

[0049] The present invention will be further described in detail below through specific embodiments.

[0050] Example 1

[0051] Step (1): Select gas-atomized spherical Cu-Zn alloy powder (Zn content 35wt%, particle size range 55–85μm) for powder pretreatment, use propanol for ultrasonic cleaning for 10min to remove organic contamination, then soak in 5wt% dilute hydrochloric acid for 1min to remove oxides, and finally rinse with deionized water until neutral and place in a 60°C drying oven for drying.

[0052] The dried Cu-Zn alloy powder and etching solution were placed in a beaker at a ratio of 1 g: 50 mL. Selective dealloying, prioritizing the dissolution of metallic Zn, was performed at room temperature, with magnetic stirring at 200 rpm to prevent powder agglomeration. The etching solution consisted of an oxidant, an inorganic acid, a corrosion inhibitor, and water. The oxidant was H₂O₂ at a concentration of 30 wt% in water (too high a concentration would lead to over-corrosion and fracture of the copper skeleton, while too low a concentration would result in incomplete Zn corrosion). Dilute H₂SO₄ (0.7 mol / L in water) was added to provide H₂ for the reaction. +The process begins by dissolving ZnO ions (too high an acid concentration will accelerate Cu dissolution and damage the framework structure). Then, benzotriazole (BTA), a corrosion inhibitor, is added at a concentration of 0.3 g / L in water. Too high a concentration will cause the BTA to form a polymer film with Cu, while too low a concentration will cause a side reaction between Cu and the oxidant, leading to the dissolution of the Cu framework. In the initial 0-10 minutes of the reaction, a large number of bubbles are formed, during which Zn dissolves rapidly. In the middle 10-30 minutes, the reaction slows down as a porous framework structure begins to form. Finally, no more bubbles are produced, indicating the reaction has terminated and the solution turns blue (Cu). 2+ (Displayed in blue). The reaction mixture was filtered to obtain a solid powder. The powder was then transferred to an ultrasonic cleaning solution for a second ultrasonic cleaning of 15 min. The cleaning solution consisted of water, ethanol, and Na2CO3 (a small amount of Na2CO3 could be added to neutralize residual acid); the volume ratio of water to ethanol was 1:1; the mass ratio of water to Na2CO3 was 50:1. Finally, the powder was freeze-dried in liquid nitrogen for 3 hours. After freeze-drying, it was allowed to rise to room temperature with air to prevent the copper framework from collapsing, resulting in a porous copper framework powder with a porosity of approximately 75%. The pore size of the obtained porous structure was mainly distributed between 5.4 and 8.1 μm, with an average pore size of 6.7 μm.

[0053] Step (2): Use a grinding wheel to remove the oxide layer and impurities from the steel alloy surface. Further treat the ground surface with anhydrous ethanol. Place the treated substrate on a preheating table for preheating to 400 degrees Celsius. Use a 1064nm laser cladding system for cladding.

[0054] The prepared Cu framework powder was placed in a drying oven and dried at 120 degrees Celsius for one hour. After cooling to room temperature, it was added to the powder feeder and local powder feeding was selected. After observing powder being fed from the laser head, the powder feeding mode was changed to external powder feeding on the powder feeder control panel. A cladding experiment was then conducted. The distance between the laser head nozzle and the 45 steel alloy substrate was set to 15 mm to ensure that the laser focus and the powder at the outlet converged. The laser head was slightly tilted at an 85-degree angle to the horizontal plane of the substrate to prevent damage to the laser head from cladding splashes. Then, a mobile... The distance between the two points was measured with calipers, and cards of equal length were made for subsequent experiments. Then, a KUKA robot was used to set the starting point for laser cladding. After setting the starting point, the powder feeding gas pressure and powder feeding rate were adjusted to preset values. The optimal powder feeding gas pressure for this invention is 0.5 MPa. After multiple tests, the powder feeding rate was set to 10 g / min, the scanning speed to 15 mm / s, and the external mode was confirmed again. The laser used for laser cladding was a 1064 nm wavelength laser; the laser power in the laser system was set to 1800 W. The laser output was then enabled, and the KUKA robot controlled the laser equipment to switch the operating mode to automatic. At this point, the laser power ensured optimal cladding results and no obvious defects such as cracks or fissures on the surface. Simultaneously, the water cooler was turned on before the experiment; the water cooler must be turned on before the laser is activated. Wear protective goggles (to prevent irreversible damage to the eyes from the laser) and observe the powder feeding of the powder feeder and the light output of the laser. If any abnormality occurs, immediately press the emergency stop button to avoid injury.

[0055] Example 2

[0056] Step (1): Select gas-atomized spherical Cu-Zn alloy powder (Zn content 35wt%, particle size range 55–85μm) for powder pretreatment, use propanol for ultrasonic cleaning for 10min to remove organic contamination, then soak in 5wt% dilute hydrochloric acid for 1min to remove oxides, and finally rinse with deionized water until neutral and place in a 60°C drying oven for drying.

[0057] The dried Cu-Zn alloy powder and etching solution were placed in a beaker at a ratio of 1 g: 50 mL. Selective dealloying, prioritizing the dissolution of metallic Zn, was performed at room temperature, with magnetic stirring at 200 rpm to prevent powder agglomeration. The etching solution consisted of an oxidant, an inorganic acid, a corrosion inhibitor, and water; the oxidant was H₂O₂ at a concentration of 30 wt% in water, and dilute H₂SO₄ (0.6 mol / L in water) was added to provide H₂ for the reaction. +ZnO is dissolved by ionization, and then benzotriazole (BTA) corrosion inhibitor is added at a concentration of 0.35 g / L in water. In the initial stage of the reaction (0-10 min), a large number of bubbles are formed, during which Zn dissolves rapidly. In the middle stage of the reaction (10-28 min), the reaction slows down, and a porous framework structure begins to form. Finally, the reaction terminates when no more bubbles are produced, and the solution color turns blue (Cu). 2+ (Displayed in blue). The reaction mixture was filtered to obtain a solid powder, which was then transferred to an ultrasonic cleaning solution for a second ultrasonic cleaning of 18 min. The cleaning solution consisted of water, ethanol, and Na2CO3; the volume ratio of water to ethanol was 1:1; and the mass ratio of water to Na2CO3 was 50:1. Finally, the powder was freeze-dried in liquid nitrogen for 3 hours. After freeze-drying, it was allowed to rise to room temperature with air to prevent the copper framework from collapsing, resulting in a porous copper framework powder with a porosity of approximately 70%. Due to the low acid concentration, the selective dissolution of Zn was relatively weak, and the pore size of the resulting porous structure was mainly distributed between 4.8 and 6.9 μm, with an average pore size of 5.6 μm.

[0058] Step (2): Use a grinding wheel to remove the oxide layer and impurities from the surface of the steel alloy. Further treat the ground surface with anhydrous ethanol. Place the treated substrate on a preheating table and preheat it to 400 degrees Celsius. Use a laser cladding system with a wavelength of 1064nm for cladding.

[0059] The prepared Cu framework powder was placed in a drying oven and dried at 120 degrees Celsius for one hour. After cooling to room temperature, it was added to the powder feeder and local powder feeding was selected. After observing powder being fed from the laser head, the powder feeding mode was changed to external powder feeding on the powder feeder control panel. A cladding experiment was then conducted. The distance between the laser head nozzle and the 45 steel alloy substrate was set to 15 mm to ensure that the laser focus and the powder at the outlet converged. The laser head was slightly tilted at an 85-degree angle to the horizontal plane of the substrate to prevent damage to the laser head from cladding splashes. Then, a mobile... The distance between the two points was measured with calipers, and cards of equal length were made for subsequent experiments. Then, a KUKA robot was used to set the starting point for laser cladding. After setting the starting point, the powder feeding gas pressure and powder feeding rate were adjusted to preset values. The optimal powder feeding gas pressure for this invention is 0.5 MPa. After multiple tests, the powder feeding rate was set to 10 g / min, the scanning speed to 15 mm / s, and the external mode was confirmed again. The laser used for laser cladding was a 1064 nm wavelength laser; the laser power in the laser system was set to 1800 W. The laser output was then enabled, and the KUKA robot controlled the laser equipment to switch the operating mode to automatic. At this point, the laser power ensured optimal cladding results and no obvious defects such as cracks or fissures on the surface. Simultaneously, the water cooler was turned on before the experiment; the water cooler must be turned on before the laser is activated. Wear protective goggles (to prevent irreversible damage to the eyes from the laser) and observe the powder feeding of the powder feeder and the light output of the laser. If any abnormality occurs, immediately press the emergency stop button to avoid injury.

[0060] Example 3

[0061] Step (1): Select gas-atomized spherical Cu-Zn alloy powder (Zn content 35wt%, particle size range 55–85μm) for powder pretreatment, use propanol for ultrasonic cleaning for 10min to remove organic contamination, then soak in 5wt% dilute hydrochloric acid for 1min to remove oxides, and finally rinse with deionized water until neutral and place in a 60°C drying oven for drying.

[0062] The dried Cu-Zn alloy powder and etching solution were placed in a beaker at a ratio of 1 g: 50 mL. Selective dealloying, prioritizing the dissolution of metallic Zn, was performed at room temperature, with magnetic stirring at 200 rpm to prevent powder agglomeration. The etching solution consisted of an oxidant, an inorganic acid, a corrosion inhibitor, and water; the oxidant was H₂O₂ at a concentration of 30 wt% in water, and dilute H₂SO₄ (0.85 mol / L in water) was added to provide H₂ for the reaction. +ZnO was dissolved by ions, and then benzotriazole (BTA), a corrosion inhibitor, was added at a concentration of 0.35 g / L in water. In the initial 0-10 min of the reaction, a large number of bubbles formed, during which Zn dissolved rapidly. In the middle 10-33 min of the reaction, the reaction slowed down, and a porous framework structure began to form. Finally, the reaction terminated when no more bubbles were produced, and the solution turned blue. The mixture after the reaction was filtered to obtain a solid powder. The powder was then transferred to an ultrasonic cleaning solution for a second ultrasonic cleaning for 18 min. The cleaning solution consisted of water, ethanol, and Na₂CO₃; the volume ratio of water to ethanol was 1:1, and the mass ratio of water to Na₂CO₃ was 50:1. Finally, the powder was freeze-dried in liquid nitrogen for 3 hours. After freeze-drying, it was brought to room temperature with air to prevent the copper skeleton from collapsing, resulting in a porous copper skeleton powder with a porosity of about 80%. Due to the high acid concentration, the pores developed further, but some copper skeleton structures showed a tendency to be over-corroded. The pore size of the obtained porous structure was mainly distributed in the range of 6.3-9.8 μm, with an average pore size of 8.2 μm.

[0063] Step (2): Use a grinding wheel to remove the oxide layer and impurities from the steel alloy surface. Further treat the ground surface with anhydrous ethanol. Place the treated substrate on a preheating table for preheating to 400 degrees Celsius. Use a 1064nm laser cladding system for cladding.

[0064] The prepared Cu framework powder was placed in a drying oven and dried at 120 degrees Celsius for one hour. After cooling to room temperature, it was added to the powder feeder and local powder feeding was selected. After observing powder being fed from the laser head, the powder feeding mode was changed to external powder feeding on the powder feeder control panel. A cladding experiment was then conducted. The distance between the laser head nozzle and the 45 steel alloy substrate was set to 15 mm to ensure that the laser focus and the powder at the outlet converged. The laser head was slightly tilted at an 85-degree angle to the horizontal plane of the substrate to prevent damage to the laser head from cladding splashes. Then, a mobile... The distance between the two points was measured with calipers, and cards of equal length were made for subsequent experiments. Then, a KUKA robot was used to set the starting point for laser cladding. After setting the starting point, the powder feeding gas pressure and powder feeding rate were adjusted to preset values. The optimal powder feeding gas pressure for this invention is 0.5 MPa. After multiple tests, the powder feeding rate was set to 10 g / min, the scanning speed to 15 mm / s, and the external mode was confirmed again. The laser used for laser cladding was a 1064 nm wavelength laser; the laser power in the laser system was set to 1800 W. The laser output was then enabled, and the KUKA robot controlled the laser equipment to switch the operating mode to automatic. At this point, the laser power ensured optimal cladding results and no obvious defects such as cracks or fissures on the surface. Simultaneously, the water cooler was turned on before the experiment; the water cooler must be turned on before the laser is activated. Wear protective goggles (to prevent irreversible damage to the eyes from the laser) and observe the powder feeding of the powder feeder and the light output of the laser. If any abnormality occurs, immediately press the emergency stop button to avoid injury.

[0065] Test method:

[0066] The cladding sample was cut into 10x10x10mm sizes using an EDM cutter. It was then polished with 400, 600, 800, 1000, 1200, 1500, 2000, and 2500 grit sandpaper to prepare a metallographic sample for coating performance testing.

[0067] Friction and wear experiments were conducted using the MS-M9000 multifunctional friction tester to simulate the material friction and wear process. The main components of this equipment include: a reciprocating friction module, a rotary friction module, a weight loading mechanism, and a display. The previously prepared coated sample and the Al2O3 ceramic balls used in the grinding pair were placed in the designated area. The test parameters were set as follows: load 20N, frequency 2Hz, stroke 5mm, and time 30min, and the test began. The real-time friction coefficient during the test was displayed on the screen. Furthermore, multiple sets of experiments were conducted on Cu skeleton powder coated samples using this equipment.

[0068] Comparative Example 1

[0069] It adopts the same technical solution as Example 1, the only difference being that Cu-Zn alloy powder is directly laser clad.

[0070] Comparative Example 2

[0071] It adopts the same technical solution as Example 1, except that the Zn content in the Cu-Zn alloy powder used in step (1) is 50wt%.

[0072] Comparative Example 3

[0073] It adopts the same technical solution as Example 1, except that the Zn content in the Cu-Zn alloy powder used in step (1) is 10wt%.

[0074] The properties of the coatings prepared by the above method are shown in Table 1 below:

[0075] Table 1

[0076] Example 1 867μm 90.4% IACS Example 2 817μm 88.6% IACS Example 3 801μm 87.1% IACS Comparative Example 1 627μm 40.3% IACS Comparative Example 2 768μm 69.7% IACS Comparative Example 3 750μm 60.8% IACS

[0077] The experimental results of Example 1 and Comparative Example 1 demonstrate that the coating prepared using the copper framework structure exhibits superior performance in both coating thickness and conductivity. These improvements in both indicators collectively confirm the significant advantages of this preparation method in improving laser energy utilization efficiency.

[0078] First, the increased conductivity directly reflects a denser internal structure and significantly reduced porosity in the coating. The essence of material conductivity lies in the directional movement of free electrons within a continuous crystal lattice. The presence of porosity disrupts this lattice continuity, hindering electron transport and thus reducing macroscopic conductivity. Therefore, the improved conductivity provides strong evidence that this method can effectively reduce internal defects in the coating and achieve high-quality metallurgical bonding. The underlying mechanism is that the unique copper framework structure causes the laser beam to undergo multiple reflections and scatterings within the powder pores, rather than being directly dissipated by the highly reflective powder surface. This process greatly promotes the complete melting of the powder, thereby reducing porosity in the final coating.

[0079] Secondly, the increased coating thickness demonstrates improved laser energy utilization and powder deposition efficiency. With process parameters such as laser power, powder feed rate, scanning speed, and powder quality remaining constant, a thicker coating means that the incident laser energy is used more effectively to melt the powder and bond it to the substrate. This is attributed to the unique microstructure of the copper framework of this invention: on the one hand, the laser beam is repeatedly captured and absorbed within the intricate framework and pores, optimizing the energy distribution along the depth of the powder layer and achieving a deep penetration effect; on the other hand, the framework structure doubles the specific surface area of ​​the powder, significantly improving energy utilization and reducing dependence on high-power near-infrared lasers.

[0080] The core of this method lies in the successful construction of a porous copper framework by directionally dissolving the Zn component in Cu-Zn composite powder using chemical reagents. This innovative structure not only improves energy utilization by enhancing the internal reflection and absorption of laser light, but also avoids problems such as substrate deformation and molten pool spatter caused by excessive heat input.

[0081] The experimental results of Example 1, Comparative Examples 2 and 3 of this invention show that coatings prepared with a specific Zn content in Cu-Zn alloy powder have better performance.

[0082] In summary, this invention improves the energy utilization rate of the laser and powder by constructing a porous Cu framework structure, increasing the multiple reflections and effective action paths of the laser inside the powder, and ensuring a tight metallurgical bond with the substrate while achieving a synergistic improvement in coating thickness and conductivity.

[0083] The above embodiments are merely illustrative examples and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a coating based on copper powder with high laser utilization rate, characterized in that, Includes the following steps: (1) Preparation of Cu framework powder; Cu-Zn alloy powder is first ultrasonically cleaned with an organic solvent, then soaked in dilute acid, washed with water and dried. Then, under stirring conditions, the dried Cu-Zn alloy powder is added to an etching solution for selective dealloying treatment with preferential dissolution of metallic Zn. Solid-liquid separation, ultrasonic cleaning twice, freeze drying and then heated to room temperature to obtain porous Cu framework powder; the Zn content in the Cu-Zn alloy powder is 30-40 wt%; the particle size of the Cu-Zn alloy powder is 45-100 μm; the porosity of the porous Cu framework powder is 60-80%; the average pore diameter of the porous Cu framework powder is 5-10 μm; the etching solution includes an oxidant, an inorganic acid, a corrosion inhibitor and water; the oxidant is H2O2; the inorganic acid is H2SO4; the corrosion inhibitor is benzotriazole. (2) The Cu skeleton powder is deposited on the substrate by laser cladding to form a coating; the laser used for laser cladding is a laser with a wavelength of 1064nm.

2. The method for preparing a coating based on high laser utilization copper powder according to claim 1, characterized in that: Step (1), The organic solvent is selected from at least one of propanol and acetone; The duration of one ultrasonic cleaning cycle is 10-30 minutes; The dilute acid is a 3-8 wt% dilute hydrochloric acid solution; The dilute acid soaking time is 50-100 seconds; The drying process is carried out at a temperature of 50-65℃.

3. The method for preparing a coating based on high laser utilization copper powder according to claim 1, characterized in that: Step (1), In the corrosive solution, the concentration of the oxidant in water is 25-35 wt%; the concentration of the inorganic acid in water is 0.5-1 mol / L; and the concentration of the corrosion inhibitor in water is 0.2-0.5 g / L.

4. The method for preparing a coating based on high laser utilization copper powder according to claim 1, characterized in that: Step (1), The stirring speed is 180-250 rpm; The ratio of dried Cu-Zn alloy powder to etching solution is 1g:40-60mL; The selective dealloying treatment was performed at room temperature. The selective dealloying treatment time is 25-60 min; The solid-liquid separation method is filtration separation.

5. The method for preparing a coating based on high laser utilization copper powder according to claim 4, characterized in that: Step (1), The cleaning solution for secondary ultrasonic cleaning includes water, ethanol, and Na2CO3; wherein the volume ratio of water to ethanol is 3-1:1; and the mass ratio of water to Na2CO3 is 50-100:

1. The second ultrasonic cleaning time is 15-20 minutes; The freeze-drying time is 2-6 hours; After freeze-drying, it rises to room temperature with the air.

6. The method for preparing a coating based on high laser utilization copper powder according to claim 1, characterized in that: Step (2), The base material is selected from 45 steel or Q235 steel; The laser power of the laser cladding is 1500-3000W; The powder feeding rate for laser cladding is set to 5-25 g / min.

7. The method for preparing a coating based on high laser utilization copper powder according to claim 1, characterized in that: Step (2), The angle between the laser head nozzle of the laser cladding and the horizontal plane of the substrate is 75-85 degrees; The distance between the laser head nozzle and the substrate in the laser cladding is set to 13-20mm; The scanning speed of the laser cladding is 10-20 mm / s.

8. The coating material prepared by the method according to any one of claims 1-7, characterized in that, The coating material has a coating thickness of 800-1000 micrometers; The conductivity of the coating material reaches 82% IACS or higher.

9. The application of the coating material as described in claim 8 in a current-carrying friction component.

Citation Information

Patent Citations

  • Method for preparing nano porous copper thin film material by magnetron sputtering

    CN105543796A

  • Method for preparing Cu micro-nano sheet structure through chemical dealloying

    CN107398554A